PENGALAMAN MAHASISWA DALAM MENGINTERNALISASI MODERASI BERAGAMA DI LINGKUNGAN KAMPUS PLURAL: STUDI FENOMENOLOGIS PADA UKM FORUM KOMUNIKASI DAKWAH KAMPUS (FKDK) UNIVERSITAS SINGAPERBANGSA KARAWANG (UNSIKA) - Andriani, Silvi; Kasja Eki Waluyo; Abdul Azis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Based on data from the National Counterterrorism Agency (BNPT), 2,670 terrorism and radicalism-laden content were found to be spread on social media. This finding indicates that Indonesia is in a worrying situation regarding the spread of radical ideology, so a comprehensive and sustainable prevention strategy is needed. This study aims to explore in depth the personal experiences of members of the Student Activity Unit of the Campus Da'wah Communication Forum (UKM FKDK) of Singaperbangsa University, Karawang in internalizing the values ​​of religious moderation in the midst of a pluralistic and multicultural campus environment. This study uses a qualitative method, the approach used in this study is a phenomenological approach through in-depth interviews with informants. This study highlights the importance of understanding religious moderation, namely a balanced and non-extremist attitude in practicing religious teachings, and how this is internalized in a pluralistic campus life. The FKDK administrators showed that their understanding of religious moderation encourages an inclusive and tolerant attitude towards differences, including not accusing others of being infidels and maintaining harmonious social relationships